Roles of Long Non-coding RNAs in the Development of Chronic Pain - Li, Zheng; Li, Xiongjuan; Jian, Wenling; Xue, Qingsheng; Liu, Zhiheng (Frontiers in Molecular Neuroscience, 2021)
Chronic pain, a severe public health issue, affects the quality of life of patients and results in a major socio-economic burden. Only limited drug treatments for chronic pain are available, and they have insufficient efficacy. Recent studies have found that the expression of long non-coding RNAs (lncRNAs) is dysregulated in various chronic pain models, including chronic neuropathic pain, chronic inflammatory pain, and chronic cancer-related pain. Studies have also explored the effect of these dysregulated lncRNAs on the activation of microRNAs, inflammatory cytokines, and so on. These mechanisms have been widely demonstrated to play a critical role in the development of chronic pain. The findings of these studies indicate the significant roles of dysregulated lncRNAs in chronic pain in the dorsal root ganglion and spinal cord following peripheral or central nerve lesions. This review summarizes the mechanism underlying the abnormal expression of lncRNAs in the development of chronic pain induced by peripheral nerve injury, diabetic neuropathy, inflammatory response, trigeminal neuralgia, spinal cord injury, cancer metastasis, and other conditions. Understanding the effect of lncRNAs may provide a novel insight that targeting lncRNAs could be a potential candidate for therapeutic intervention in chronic pain.